DIKSI DAN GAYA BAHASA PADA IKLAN LAYANAN MASYARAKAT DI RADIO SEBAGAI MATERI AJAR DI SMP - Nindy Kariska; Andayani Andayani; Atikah Anindyarini (Universitas Sebelas Maret, 2019)
The purpose of this study is to describe: (1) use of diction in public service advertisements on the radio, (2) use of the style language public service advertisements on the radio, and (3) the relevance of the study with teaching material in junior high school. This research uses qualitative descriptive method. The data source in this research is the recorded public service announcements that were broadcast by radio Gesma. Sampling using a purposive sampling. Engineering data collection using the technique, refer to the record, record, and in-depth interviews. The validity of this research data using triangulation of data sources and theories. This research data analysis using the method of Flow Model of Analysis. The results of the analysis of the findings regarding the use of diction and style of advertising language is described as follows. The first use of diction public service advertisements on the radio is dominated by the word gaul. The use of the words based on the context of the speech, target audience, purpose and message delivery information the ad with an interesting language and communicative, and easily understood by the audience. Second, the use of stylistic rhetoric dominates the results. The use of stylistic variation, giving a characteristic flavor, and the value on ads aired. Third, the research results in the form of diction and style of language in public service advertisements on the radio can be direlevansikan on a language learning curriculum revision in 2013 Indonesia junior high school class VIII.